Effect of retirement on medical reimbursement expenses—evidence from China - Yuanyang Wu; Jiahui Pang; Hualei Yang (Health Economics Review, 2023)
Abstract Background Medical reimbursement in China is not for all diseases, and medical reimbursement expenses are not completely consistent with medical service demand, though the scope and proportion of medical reimbursement are gradually expanding. This study aimed to examine the effect of retirement on medical reimbursement expenses in urban China. Methods The effect of retirement on medical reimbursement expenses were estimated by using fuzzy regression discontinuity based on data from the China Health and Retirement Longitudinal Study (CHARLS) in 2011, 2013, 2015, and 2018. Its group heterogeneity by educational backgrounds and marital status, and underlying mechanisms were also explored. Results Retirement increased medical reimbursement expenses of outpatient significantly (P < 0.05).Low time cost and deteriorating health status after retirement were possible mechanisms in this association. Retirement increased the reimbursement expenses significantly among the older adults with more educational obtainment or being widowed/divorced. Conclusion The above findings indicated that there was a positive association between retirement and medical reimbursement expenses. The scope and proportion of medical reimbursement should be incorporated into retirement policy for improving medical service accessibility and rational healthcare utilization of retired population.